Research on choices of methods of internet of things pricing based on variation of perceived value of service - Wei Li; Lijun Mei; Kai Nie (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: With the rapid progress of Internet of Things technology, the information service of IoT has got unprecedented development, and plays an increasingly important role in real life. For the increasing demand of information service, the pricing of information service becomes more important. This paper aims to analyze the strategic options and payoff function between information provider and intermediaries based on Stackelberg game. Firstly, we describe information service delivery method based on the Internet of Things specific function. Secondly, we calculate the consumer demand for the information service. Finally, we explain two kinds of strategic options by the game theory, and then discuss the optimal pricing method of information services based on profit maximization. Design/methodology/approach: To achieve this objective, Considering the consumer perceived value of Internet of Things Service changing, we establish a Stackelberg model in which the supplier is the leader followed by the middleman. Then, we compare the advantages of using individual pricing with that of bundling pricing. Findings: The results show that whether information providers adopt bundling pricing strategy or individual pricing strategy depends on the cost of perception equipment, if information providers want to adopt individual pricing strategy, the variation of consumers' perception value of information services must meet certain conditions. Research limitations/implications: the providers make price for the information service, in addition to continuously improve the quality of information service, it also devotes resources to tapping and understanding market information, such as the sensor device price, the variation of perception value of information services and so on, so as to create competitive advantage. This paper is just a preliminary model, it does not take into account the effect of mixed bundling. Originality/value: In this research, a new model for price information service with the game theory is proposed. To the authors' knowledge, it is the first time to study the pricing of information service with the game theory, It discuss the impact of consumers' perceived value for the equipment of internet of things on pricing strategy, and it also analyze the impaction of consumers' perceived value for information service on pricing strategy, the research shows that the information providers should take different strategies based on the specific situations to maximize the profit on the information service market of the IOT.
Keywords: 650; Internet of things; individual pricing; bundling pricing; services pricing